2018
DOI: 10.1071/ah16200
|View full text |Cite
|
Sign up to set email alerts
|

Health and well being of lesbian, gay, bisexual, transgender and intersex people aged 50 years and over

Abstract: Objectives The aim of the present study was to examine the health and well being of older lesbian, gay, bisexual, transgender and intersex (LGBTI) people, the health issues that concern them, the services they use and challenges accessing services. Methods This study comprised a survey of the health and well being of 312 LGBTI people aged 50 years and over in New South Wales. The survey included the Short-Form 12 (SF-12) measure of health-related quality of life, the Kessler 10 (K10) measure of psychological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
2
28
3
Order By: Relevance
“…There were no differences between care‐givers and non‐caregivers on these variables among the men or women after adjusting for socio‐demographic variables. These results are somewhat inconsistent with previous research, which has found that lesbian and gay care‐givers experience poorer mental health than non‐caregivers (Fredriksen‐Goldsen et al, ; Hughes, ), although not all studies making this comparison have found such differences (Grossman et al, ). This may be due to the fact that these previous studies adjusted for fewer (Fredriksen‐Goldsen et al, ) or no socio‐demographic variables (Hughes, ).…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…There were no differences between care‐givers and non‐caregivers on these variables among the men or women after adjusting for socio‐demographic variables. These results are somewhat inconsistent with previous research, which has found that lesbian and gay care‐givers experience poorer mental health than non‐caregivers (Fredriksen‐Goldsen et al, ; Hughes, ), although not all studies making this comparison have found such differences (Grossman et al, ). This may be due to the fact that these previous studies adjusted for fewer (Fredriksen‐Goldsen et al, ) or no socio‐demographic variables (Hughes, ).…”
Section: Discussioncontrasting
confidence: 92%
“…These results are somewhat inconsistent with previous research, which has found that lesbian and gay care-givers experience poorer mental health than non-caregivers Hughes, 2017), although not all studies making this comparison have found such differences (Grossman et al, 2007). This may be due to the fact that these previous studies adjusted for fewer or no socio-demographic variables (Hughes, 2017 et al, 2016). It may therefore be possible that this particular sample had more participants for whom potential benefits of being a care-giver offset some of the costs.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations